2010
DOI: 10.1111/j.1365-313x.2010.04323.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and water homeostasis analysis of Thellungiella salsuginea suggests that dehydration tolerance is a key response to osmotic stress in this halophyte

Abstract: Metabolome and water homeostasis analysis of Thellungiella salsuginea suggests that dehydration tolerance is a key response to osmotic stress in this halophyte SUMMARYThellungiella salsuginea, a Brassicaceae species closely related to Arabidopsis thaliana, is tolerant to high salinity. The two species were compared under conditions of osmotic stress to assess the relationships between stress tolerance, the metabolome, water homeostasis and growth performance. A broad range of metabolites were analysed by meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 78 publications
(154 reference statements)
9
113
0
2
Order By: Relevance
“…7). This results is consistent with findings in S. salsa and Thellungiella salsuginea (Lugan et al 2010;Wu et al 2012). These results suggest that salinity restrain amino acid metabolism in S. corniculata which may lead to a reduction of organic acids because it would lessen the capacity of osmotic adjustment under salt stress.…”
Section: Protein Processing and Amino Acid Metabolismsupporting
confidence: 82%
“…7). This results is consistent with findings in S. salsa and Thellungiella salsuginea (Lugan et al 2010;Wu et al 2012). These results suggest that salinity restrain amino acid metabolism in S. corniculata which may lead to a reduction of organic acids because it would lessen the capacity of osmotic adjustment under salt stress.…”
Section: Protein Processing and Amino Acid Metabolismsupporting
confidence: 82%
“…To elucidate the function of a single compound, it is also important to be aware that compensatory mechanisms are commonplace and that a change in the content of a single metabolite may have no effects on the phenotype, because of compensative modulation of other components of the same family of compounds. The original approach proposed by Lugan et al (2010), considering the metabolome as a single "virtual molecule" whose physicochemical properties are the weighted averages of www.intechopen.com the properties of individual metabolites, also appears to be quite promising both to investigate the global metabolic strategies of a species to maintain cell function under stress and to evaluate differences among species. In addition, further efforts to make stress treatment conditions more relevant to plant growth outside of the lab are required.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolome data, together with transcriptome results, have pointed towards the presence of a stress anticipatory strategy in Thellungiella as responsible for its "extremophile" characteristics. More recently, Arabidopsis and Thellungiella responses to salinity and osmotic stress have been compared with an analogous approach by Lugan et al (2010). The authors found that, apart from a few differences in raffinose and secondary metabolites, salt stress affected the same metabolic pathways in the two species, the main differences being quantitative.…”
Section: Salt Stress Response: Thellungiella Vs Arabidopsismentioning
confidence: 99%
See 1 more Smart Citation
“…The auxin synthesis and transport offered the plant to adapt various stress [13]. Amino acids deposition has been observed in many plants exposed to abiotic stress [14]. Citrate synthase is an enzyme responsible for the catalyzing the reaction of the citric acid cycle the condensation of acetyl-coA and oxaloacetate to form citrate [15].…”
Section: Introductionmentioning
confidence: 99%